MODIFICATION OF SMILE TECHNOLOGY IN AMETROPIA CORRECTION - O. V. Pisarevskaya; T. N. Iureva; A. G. Shchuko; E. P. Ivleva; T. N. Frolova (Acta Biomedica Scientifica, 2016)
Purpose: To evaluate the clinical efficacy and safety of modified SMILE surgery for mild myopia. Methods: The study involved 68 patients (135 eyes), operated by SMILE methods for mild myopia. The first group included patients operated by standard technology with a l5 ßm thickness of neural optical lenticular layer, the second group - patients, operated by a modified SMILE technology monolayer with thickness of 30 μm. A comprehensive ophthalmology examination was performed before the surgery and after the surgical treatment - on the following day, in one month and in 12 months. Results: In all patients of both groups the monocular uncorrected visual acuity after the operation after the period of one day, one month, and a year did not differ and made 0.88 ± 0.15, 0.92 ± 0.1 and 0.95 ± 0.08 respectively, for the second group - 0.87 ± 0.18, 0.92 ± 0.15 and 0.96 ± 0.10 (p > 0.05). Follow-up in the early and late postoperative period convincingly demonstrated that visual acuity, refraction, spatial sensitivity, corneal hysteresis indices and even a subjective assessment of visual quality have no statistically significant differences among patients in both groups. During the operation and late postoperative period the complications were not noted. Conclusion: the study found that the modified technology provides high visual acuity, while minimally changing the biomechanical properties of the cornea. Thus, a modified SMILE operation is highly predictable and safe method in correction of slight degree myopia.